RESPONS PERTUMBUHAN DAN HASIL TIGA VARIETAS CAISIM TERHADAP PEMBERIAN PUPUK ORGANIK CAIR BIOMETHAGREEN - Bhaskara Anggarda Gathot Subrata; Benita Erningpraja martha (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2017)
The study was conducted at Screen house of Department of Agrotechnology, College of Agriculture Petra Baliem Wamena. Altitude of place ± 1680 m asl June - July 2017. This research is a factorial experiment with the basic design of Randomized Completed Block Design (RCBD). This study consists of two factors that are arranged factorially. The first factor is the concentration of liquid organic fertilizer BioMethaGreen consisting of: without liquid organic fertilizer BioMethaGreen, 15 cc / l, 30cc / l. The second factor is caisim crop varieties which include: Tosakan varieties, Shinta varieties, Local varieties. The variables observed were plant height, leaf number, leaf area, wet crop weight, dry plant weight, and root volume. The results showed that the use of liquid fertilizer BioMethaGreen does not give effect to all growth variables and caisim plant yield. The use of three caisim varieties has a very real effect on all variables. There is no interaction between the use of BioMethaGreen liquid organic fertilizer and the use of three caisim varieties.